1988
DOI: 10.1530/jrf.0.0830673
|View full text |Cite
|
Sign up to set email alerts
|

Sweat glands of the scrotum of the bull

Abstract: Summary. Skin samples were taken post mortem from the scrotum, abdomen and neck of 4 mature bulls. The volume of sweat glands per unit skin surface area of the scrotum was greater than that of other body regions. Within the scrotum there was a gradient in sweat gland volume increasing from proximal through to distal parts of the scrotum. These results suggest a previously unidentified variable cooling capacity of the scrotum depending on testicular descent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
3

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
0
10
0
3
Order By: Relevance
“…Several factors contribute to scrotal and testicular thermorégulation including the structure of the scrotum which holds the testes away from the body (Carrick and Setchell, 1977) and the testicular vascular cone which reduces testicular temperature by both countercurrent heat exchange (Gunn and Gould, 1975;Cook et al, 1994) and radiation from the scrotal surface (Coulter, 1988). In addition, the tunica dartos muscle affects the location of the testes relative to the body (Setchell, 1978) and scrotal sweat glands provide evaporative cooling (Blazquez et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors contribute to scrotal and testicular thermorégulation including the structure of the scrotum which holds the testes away from the body (Carrick and Setchell, 1977) and the testicular vascular cone which reduces testicular temperature by both countercurrent heat exchange (Gunn and Gould, 1975;Cook et al, 1994) and radiation from the scrotal surface (Coulter, 1988). In addition, the tunica dartos muscle affects the location of the testes relative to the body (Setchell, 1978) and scrotal sweat glands provide evaporative cooling (Blazquez et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Close attachment of these fibers with the vascular wall is another factor regulating the thermoregulation in the scrotum [11]. Beside dartos and cremaster muscles, pampiniform plexus also plays role in the thermoregulation of testes [12]. Wright et al [13] reported a decrease in testicular temperature after varicocelectomy in infertile men.…”
Section: Discussionmentioning
confidence: 99%
“…Mieusset et al [17] measured the temperatures of the testes, scrotum and the Bogros space and found significant differences between undescended and descended testes. Blazquez et al [12] reported that scrotal sweat glands have an important role in thermoregulation of the testes, which are mostly found in the distal part of the scrotum in bulls. They believe that the density of the sweat glands in the scrotum also has an effect on testicular temperature besides dartos contraction and sweat discharge [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of these factors are the evaporation produced by the sweat glands (Blasquez et al 1988, Dyce et al 2004, Nunes 2005, the contraction and relaxation of the cremasteric muscle and dartos tunic responsible for the testicle approximation and coming away in relation to the body (Banks 1991, Hafez & Hafez 2003, and the scrotal sanguine flow which is responsible for the heat irradiation (Brito et al 2004) and the upstream mechanism flow made by the spermatic internal artery in relation to the downstream flow occasioned by the testicular veins (Getty 1986, Godinho et al 1987, Setchell et al 1988, Almeida 2003, Hafez & Hafez 2003, Brito et al 2004, Dyce et al 2004.…”
Section: Introductionmentioning
confidence: 99%